Secured ATM Pin Recovery Using Fingerprint Technology and OTP Verification - Linda John, Rutik Gharat, Kunal Patere, Aniket Patil (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In the existing system, user go to ATM center then user inserts an ATM card into ATM machine then enters the pin for authentication. User will get three chances to enter the right pin, if user unable to enter right pin in three attempts then user get chance to set a new pin. If the user unable to enter the right pin after three chances, the card gets block automatically and to reactivate the ATM card user will have to go to the particular bank. We have designed a system that allows users to reset ATM password at ATM center itself, by identifying fingerprint and OTP. User will get OTP on user’s registered mobile number. The main objective of this technology is to avoid time consumption. As user can reactivate ATM card in ATM center itself, user can save plenty of time.